Buckling analysis and design optimization of trapezoidal composite plates under hygrothermal environments. (1st July 2023) - Yas, M.H.; Bayat, A.; Kamarian, S.; Malekshahi, A.; Song, J.I.
Abstract: The main goal of the present work is to study the buckling analysis and optimization of trapezoidal composite plates under hygrothermal conditions. The stability equations are first derived based on the first-order shear deformation theory (FSDT) using the energy method. Then, the generalized differential quadrature (GDQ) method is implemented to calculate the critical buckling temperature and moisture content. The effects of various parameters such as temperature, humidity, lay-up, boundary conditions, and geometry are also examined on the stability of trapezoidal composite plates. The numerical results indicate the significant effects of high-temperature and high-humidity environments on the buckling response of the structure. Finally, genetic algorithm (GA) is used to optimize the arrangement of layers for maximum buckling load. The optimization results are obtained to indicate the effecs of geometric parameters, boundary conditions, and hygrothermal loads on the optimal design of trapezoidal composite plates.